1993
DOI: 10.1002/chin.199330078
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Conversion of Levoglucosenone in Acidic Media.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Moreover, the formation of AGF and AGP as “side-equilibria” analogous to the formation of AFF from fructose is also possibly the case, which also explains why glucofuranoses are not favored glucose isomers but AGF is still relatively abundant in solution in comparison to AGP. The dehydration of AGP in liquid phase has not been well studied; however, it has been suggested that the hydration of AGP to glucose is the first step in the reactions leading to HMF. , However, the presence of AGF and AGP suggests that the conversion of glucose to HMF may also proceed through AGF and AGP . We have also confirmed that LGN can be converted to HMF with added 5 mol/L H 2 SO 4 at 130 °C in up to 65% yield in only 4 min and reaching almost 80% LA and FA by further heating.…”
Section: Results and Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, the formation of AGF and AGP as “side-equilibria” analogous to the formation of AFF from fructose is also possibly the case, which also explains why glucofuranoses are not favored glucose isomers but AGF is still relatively abundant in solution in comparison to AGP. The dehydration of AGP in liquid phase has not been well studied; however, it has been suggested that the hydration of AGP to glucose is the first step in the reactions leading to HMF. , However, the presence of AGF and AGP suggests that the conversion of glucose to HMF may also proceed through AGF and AGP . We have also confirmed that LGN can be converted to HMF with added 5 mol/L H 2 SO 4 at 130 °C in up to 65% yield in only 4 min and reaching almost 80% LA and FA by further heating.…”
Section: Results and Discussionsupporting
confidence: 69%
“…34,35 However, the presence of AGF and AGP suggests that the conversion of glucose to HMF may also proceed through AGF and AGP. 36 We have also confirmed that LGN can be converted to HMF with added 5 mol/L H 2 SO 4 at 130 °C in up to 65% yield in only 4 min and reaching 80% LA and FA by further heating. The numerous pathways available for acid-catalyzed conversion of glucose to HMF makes determining which pathways are the most dominant challenging, and this will be the subject of a future publication.…”
Section: ■ Results and Discussionmentioning
confidence: 99%